Healthcare Worker Vulnerability and COVID-19 Panic, Tension and Distrust Through the Perspective of Social Media in Indonesia - Najmah; Davies, TG; Kusnan; Candra, R; Andajani, S; Davies, SG (Australian National University (ANU), 2024)
This paper explores the intersection of COVID-19 and panic in Indonesia, with the aim of analysing four factors driving panic during the 2020–2022 pandemic: limited access to personal protective equipment (PPE); delayed diagnosis of COVID-19 among clusters of health workers; distrust of health services; and amplification of distrust and misinformation through social media, particularly about the role of health workers. We employ an intersectional lens to analyse the complex social positions, cultural gender norms and roles that influence the experiences and perceptions of male and female health workers during the pandemic. Through six case studies involving three doctors, two nurses and one midwife, all of whom tragically succumbed to the virus within the first 16 months of the pandemic, this research highlights the need for the Indonesian public health system to prepare for further pandemics and to ensure the capacity of the Indonesian public health system for its preparedness and resilience for future health emergencies or crises.
Keywords: 1608 Sociology; 1699 Other Studies in Human Society; 2002 Cultural Studies; 4401 Anthropology; 4405 Gender studies; 4410 Sociology